ARTISTIC AND COMPOSITION FEATURES OF CHILDREN’S COSTUME IN THE HIGH FASHION COLLECTIONS IN THE 20TH AND EARLY 21ST CENTURY - Герасименко, О. Д.; Пашкевич, К. Л.; Омельченко, Г. В.; Загрійчук, Б. П.; Колосниченко, О. М. (Art and Design, 2020)
The purpose of the work is to study the artistic and compositional features in children’s collections of haute couture houses and determine the patterns of their repetition in the design of children’s costumes in the 20th and early 21st century. To achieve this goal, a historical study of materials, a visual-analytical method, morphological and compositional-structural analysis were applied. The evolution of children’s costume in the high fashion collections in the and early 21st century is investigated and the main trends in children’s fashion for a given period of time are analyzed. The artistic and compositional features of the children’s costume are identified, the most characteristic artistic and structural elements of children’s clothing are identified: three-dimensional shape, color scheme and fabric pattern, structural and decorative elements and decoration. The regularity of repeating the pattern of fabric in the collections of children’s clothing of the Fashion houses in the 20th and early 21st century is established. The collected materials and their analysis made it possible to establish regularity of repeating of artistic and compositional features in a children’s costume, such as a fabric pattern and decoration in different years in models of children’s clothing of High Fashion Houses. Practical significance lies in the generalization of artistic compositional features and the identification of leading trends in the artistic compositional solution of children’s costumes in the high fashion collections in the 20th and early 21st century. The results will make it possible to predict trends in children’s fashion, design actual models of clothing for children and can be used in further research on the design of children’s clothing.